Three-dimensional polarization amplitude modulator and demodulator - Han-bin SONG; Jun-bo ZHANG; Xiao-guang CHEN; Jian-qiu ZHANG (Tongxin xuebao)
Based on the mathematical description of a space electromagnetic field,a novel approach to the three-dimen-sional joint modulation of the signal amplitude,polarization angle and polarization phase angle of an electromagnetic signal in wireless communication was presented.The model of the three-dimensional modulation signal was first given by the equations of the relationship among the parameters of a space electromagnetic field.Then,the transmission im-plementation of the three-dimensional joint modulation signal was discussed by a vector antenna.At the receiving end,a signal amplitude detection and DOA polarization parameter estimation method was given to demodulate the received three-dimensional joint modulation signal.The bit error rate and performance of the proposed three-dimensional joint modulator and demodulator were analyzed.Both the analysis and the simulation results show that a high information transmission and a low bit error rates can simultaneously be obtained by the proposed method.